Management protocols of chronic Orofacial Pain: A Systematic Review - Harsh Priyank; Ravi Shankar Prasad; Sahana Shivakumar; Nishath Sayed Abdul; Anuja Pathak; Gabriele Cervino; Marco Cicciù; Giuseppe Minervini (Elsevier, 2023)
Objective: Chronic orofacial pain (CP) is a persistent and debilitating condition that affects the face, mouth, and jaw and can have a significant impact on an individual's quality of life by posing problems to eat, speak, and perform everyday activities. By the means of this narrative review, we aim to assess different types of management modalities that exist to combat chronic orofacial pain. Design: Various databases were explored with MeSH keywords of chronic orofacial pain, orofacial pain, and interventions and treatment protocols for eligible articles. After an extensive literature search, it was ascertained that this review identified four major categories of treatment modalities for the management of chronic orofacial pain, namely pharmacological management, psychological management, lifestyle interventions-based management, and current stimulation-based management. Results: Of the four categories discussed, although pharmacological intervention offered the most immediate relief-especially from orofacial pain that was of a sudden, stab-like in nature-psychological management demonstrated a remarkable ability to reduce/alleviate the more serious aspect of chronic orofacial pain and was deemed better in comparison to the rest. Lifestyle-based techniques and current stimulation-based management were of limited use since they tended to focus more on the causal and not the symptomatic aspect of orofacial pain. Conclusions: Many patients with persistent orofacial discomfort can experience notable improvements in their symptoms and general well-being by all the treatment modalities evaluated.